2022
DOI: 10.3390/mps5060091
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Analysis of Maxillary Canine Impaction through Sella Turcica Bridging, Ponticulus Posticus Calcification, and Lateral Incisor Anomalies: A Retrospective Observational Study

Abstract: Maxillary canine impaction is an increasing dental anomaly and is often related to other dento-skeletal anomalies. The aim of this work is to support the clinician in evaluating the relationship between a displaced maxillary canine and clinical (the features of lateral incisors)/skeletal (ponticulus posticus and sella turcica bridging) anomalies through orthopanoramic radiographs, lateral cephalograms, and plaster casts to identify the parameters that best predict maxillary canine impaction. A retrospective ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It was found that, a statistically significant correlation between the maxillary canine impaction with female gender, sella turcica bridging, calcification of ponticulus posticus, and the lateral incisor anomaly [22]. These factors were observed to be the significant variables and positive predictors of maxillary impacted canines, mainly related to the impaction in the palatal region.…”
Section: Discussionmentioning
confidence: 89%
“…It was found that, a statistically significant correlation between the maxillary canine impaction with female gender, sella turcica bridging, calcification of ponticulus posticus, and the lateral incisor anomaly [22]. These factors were observed to be the significant variables and positive predictors of maxillary impacted canines, mainly related to the impaction in the palatal region.…”
Section: Discussionmentioning
confidence: 89%
“…As NCCs are a multipotent embryonic cell population that contributes to the formation of the sella turcica, teeth and atlas, if a mutation occurred in this stage, two or more congenital anomalies could be present [ 36 ]. Some dentoskeletal anomalies in the midface and neck area, such as maxillary canine impaction (MCI), atlas posterior arch deficiency (APAD) and sella turcica bridging (SB), and lateral incisor anomalies and their possible correlation with PP were analyzed by some authors due to the same or similar genetic origin [ 27 , 37 , 38 ]. The sella turcica region is an important landmark during cephalometric analysis, so it is easy to detect by orthodontists [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%